2014
DOI: 10.3133/pp18015
|View full text |Cite
|
Sign up to set email alerts
|

Magma supply, storage, and transport at shield-stage Hawaiian volcanoes

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS (1-888-275-8747) For an overview of USGS information products, including maps, imagery, and publications, visit http: //www.usgs.gov/pubprod To order this and other USGS information products, visit http://store.usgs.gov Any use of trade, firm, or product names is for descriptive purposes only and does not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
179
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(210 citation statements)
references
References 0 publications
20
179
0
Order By: Relevance
“…The vents for both these eruptions were located inside KīlaueaÕs summit caldera and these storage depths are consistent with the inferred depth of the main sub-caldera reservoir (Poland et al, 2014). In contrast the embayment from Kīlauea Iki ep.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The vents for both these eruptions were located inside KīlaueaÕs summit caldera and these storage depths are consistent with the inferred depth of the main sub-caldera reservoir (Poland et al, 2014). In contrast the embayment from Kīlauea Iki ep.…”
Section: Discussionsupporting
confidence: 77%
“…The simplified plumbing system shown is to illustrate the constraints on ascent given by the embayment models and does not reflect the actual complexities of melt storage beneath Kīlauea (e.g. see Poland et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle ERZ is dominated by low-V p ∕V s ratios (<1.7) from 0 to 15 km depth. Poland et al [2013] suggested that the increased supply at Pu'u 'O'o-Kupaianaha during 2003-2007 must have been driven by increased flux of magma from the mantle, which is supported by increased CO 2 emissions. The low-V p and low-V p ∕V s anomalies observed in our model are consistent with the existence of CO 2 and were also observed by Hansen et al [2004].…”
Section: Kilauea Volcanomentioning
confidence: 99%
“…Perhaps caldera formation results from reduction in magma supply to the shallow storage reservoir, a term we use for a confi guration of multiple magma storage volumes (Fiske and Kinoshita, 1969;Dawson et al, 2004;Baker and Amelung, 2012;Poland et al, 2014). If magma supply dropped signifi cantly, eruptions or intrusions might deplete the shallow reservoir, eventually leading to collapse of the overlying edifi ce.…”
Section: Relation Of Caldera To Cyclesmentioning
confidence: 99%